A SOCIO PRAGMATICS ANALYSIS OF REFUSAL UTTERANCES IN COMEDY MOVIE MANUSCRIPTS - WARDHANI , SANDHITYA KUSUMA (2011)
This research paper aims at finding the implicatures and politeness strategies of refusal utterances. The object is refusal utterances in comedy movie manuscripts entitled Juno. The data are sentences which shows refusal utterances. The writer uses descriptive qualitative research. Techniques of data collection used by the writer are observations and non-participant documentations by selecting refusal utterances, which can be found in comedy movie manuscripts entitled Juno. In clarifying the implicatures of refusal utterances, the writer applies theory of context situation by Hymes and the cooperative principle by Grice's maxims. To describe the politeness strategies, the writer applies politeness theory by Brown and Levinson. The results of the study show that, first there are 7 implicatures of refusal utterances based on Hymes and supports by Grice's maxims theory. They are 5 expressing anger, 8 expressing disagreement, 2 expressing dislike, 2 expressing disbelief, 4 expressing solidarity, 5 expressing blaming, and 4 expression confusion. The maxims theory that used are Follow the Maxim of Quality (7), Follow the Maxim of Quantity (8), Follow the Maxim of Relevance (1), Follow the Maxim of Manner (7), Violates Maxim of Quality (4), Violates Maxim of Relevance (2) and Violates Maxim of Manner (1). Second, by employing theory of politeness by Brown and Levinson, there are 4 types of politeness strategies used in refusal utterances in comedy movie manuscripts. They are bald on record strategy (33,3%), positive politeness (50%), negative politeness (10%), and of- record strategy (6,6%).